2020
DOI: 10.5194/isprs-archives-xliv-m-1-2020-451-2020
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Hbim to Improve the Efficiency of Visitor Flow Management in Heritage Sites. Towards Smart Heritage Management

Abstract: Abstract. Providing public access to heritage promotes a social interest in its conservation but, at the same time, it poses a risk to the conservation of resources. The biggest challenge in managing public use of heritage is to establish a sustainable relationship between heritage and tourism. The multidisciplinary teams involved in visitor flow management generate and exchange information about the heritage property without an integrative vision. The lack of a reliable, unified and up-to-date source of infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Salvador-García's [5] research has already pointed to the feasibility of managing the public use of a monument through HBIM. Following this research, it was possible to verify that the Autodesk Revit software fully allows the incorporation of information, both geometric and semantic, generated by the individuals involved in the planning and management of a cultural visit in the HBIM model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salvador-García's [5] research has already pointed to the feasibility of managing the public use of a monument through HBIM. Following this research, it was possible to verify that the Autodesk Revit software fully allows the incorporation of information, both geometric and semantic, generated by the individuals involved in the planning and management of a cultural visit in the HBIM model.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific literature has since revealed the potential of HBIM for documenting existing buildings [3] and managing various aspects related to the maintenance and preventive conservation of property [4]. Recently, it has been found that HBIM offers a great capacity for the management of public use and, specifically, of cultural tourism [5].…”
Section: Introductionmentioning
confidence: 99%
“…Among these new tools and methodologies that can help calculate the carrying capacity of heritage sites, Heritage Building Information Modelling (HBIM) stands out, as exhibited in the work of Salvador-García et al [34], who analyse and zone visiting areas in a digital model. On the other hand, Geographic Information Systems (GIS) should also be mentioned, as applied in the studies of Makhadmeh et al [35] and Simou et al [4], who analyse the density of visitors to archaeological sites.…”
Section: Background and State Of The Artmentioning
confidence: 99%
“…Next, we determined the Usable Surface for Visitation (USV), which is defined as the area that remains available for recreational visiting activities after discarding all spaces that are not useable for reasons of conservation, safety, fragility, incompatibility of uses, or due to the distribution of their components [19,34]. Similarly, areas parallel to walls and other edges have been excluded from the calculation of the Usable Surface for Visitation (USV), either for conservation reasons or because of the repulsive force that obstacles exert on people when deciding where to walk [42].…”
Section: Spatial Analysismentioning
confidence: 99%
“…Currently, limited research exists on the use of HBIM and GIS methodologies for managing tourist visits, with the exception of Salvador's team's work (Salvador-García et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%